VOTING DEVICES IN TESTING PRECONCEPTS - KAINZOVA, Veronika; Jan, RIHA; KORENA, Daniela (Trends in education, 2010)
The article introduces results of testing pre-concepts in science with usage of voting devices. Pre-concepts are an individual characteristic of each learning person. Pre-concepts are formed by various influences (school, home, native country, etc.) and the experiences. The aim of these researches resides in the pursuit of ``breaking'' the mistaken transcendental images and, of course, in teachers and pupils awareness of the most frequent errors in the preconcepts organization. Pre-concepts researches and the concepts changes are the basis of the constructivist conception of the scientific education.
Keywords: preconcept; misconcept; voting device.